Penerapan Histogram Equalization pada Optical Character Recognition Preprocessing - Peter Pangestu (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2015)
In this paper, we will discuss about the implementatoion of Histogram Equalization for images contrast enhancement, in the preprocessing step, on Optical Character Recognition(OCR). OCR has several steps, including preprocessing step. Implementing images contrast enhancement algorithm will make it easier. It is important for images to have high level contrast. It makes those images clear. Changing the histogram will make the colors of images also change. The output will be taken to the next step processing and we will get more accurate recognition.